NAVOI, GAFUR GHULAM, ERKIN VAHIDOV (Neo Science Peer Reviewed Journal, 2023)
The article talks about the commonality and skill of creators reflected in the works of Navoi, Gafur Ghulam, Erkin Vahidov, the artistic skills reflected in the works of Gafur Ghulam and Erkin Vahidov, and their works that served the development of the Turkish language.